The quantification of sodium intake from discretionary salt intake in New Zealand using the lithium-tagged salt method - Wang, Nan Xin; McLean, Rachael M.; Cameron, Claire; Skeaff, Sheila A. (Frontiers in Nutrition, 2023)
Introduction Discretionary salt (added in cooking at home or at the table) is a source of sodium and iodine in New Zealand. The amount of discretionary salt consumed in a population has implications on policies regarding sodium and iodine. Sodium intake from discretionary salt intake has not been quantified in New Zealand. The aim of this study was to estimate the proportion of total sodium that comes from discretionary salt in adults using the lithium-tagged salt method. Methods A total of 116 healthy adults, who were not pregnant or breastfeeding, regularly consume home-cooked meals and use salt during cooking or at the table, aged 18–40 years from Dunedin, New Zealand were recruited into the study. The study took place over a 9-day period. On Day 1, participants were asked to collect a baseline 24-h urine to establish their normal lithium output. From Day 2 to Day 8, normal discretionary salt was replaced with lithium-tagged salt. Between Day 6 and Day 8, participants collected another two 24-h urine samples. A 24-h dietary recall was conducted to coincide with each of the final two 24-h urine collections. Urinary sodium was analysed by Ion-Selective Electrode and urinary lithium and urinary iodine were analysed using Inductively Coupled Plasma Mass Spectrometry. The 24-h dietary recall data was entered into Xyris FoodWorks 10. All statistical analysis were conducted using Stata 17.0. Results A total of 109 participants with complete 24-h urine samples were included in the analysis. From the 24-h urine collections, the median urinary excretion of sodium and iodine was 3,222 mg/24 h (25th, 75th percentile: 2516, 3969) and 112 μg/24 h (82, 134). The median estimated sodium intake from discretionary salt was 13% (25th, 75th percentile: 7, 22) of the total sodium intake or 366 mg/24 h (25th, 75th percentile: 186, 705). Conclusion The total sodium intake was higher than the suggested dietary target of 2,000 mg/day. In this sample of healthy adults 18 to 40 years old, 13% of total sodium intake derived from discretionary salt. Discretionary salt is an additional source of iodine if iodised salt is used. Policies to reduce sodium intake is recommended to include a range of strategies to target discretionary and non-discretionary sources of salt and will need to take into account the contribution of iodine from discretionary salt intake.